Measuring the Reliability of Postural Sway Measurements for a Static Standing Task: The Effect of Age - Lo, Pei-Yi; Su, Bo-Lin; You, Yu-Lin; Yen, Chen-Wen; Wang, Shih-Ting; Guo, Lan-Yuen (Frontiers in Physiology, 2022)
Background: A force plate is used to determine the ability to balance ability. However, only some medical centers or laboratories are equipped with force plates because they are costly so a low-cost force plate is required for home care or health care institutes. Few studies compare the reliability of postural sway measurements in terms of age. This study proposes a low-cost force plate to select reliable parameters to evaluate postural sway. Objectives: To determine the intra-rater reliability of a novel force plate and the effect of age difference on the intra-rater test-retest reliability for the center of pressure (COP). Methods: Forty participants were enrolled for this study: 20 youths and 20 older adults. Participants stood on a custom-made and low-cost force plate with eyes opened and eyes closed to measure COP-related parameters. The within-day test-retest reliability was measured at two sessions on the same day and the between-days reliability was measured on two different days. The COP-related parameters include the average velocity of COP, the average velocity in the antero-posterior and medio-lateral directions, the mean distance of COP and the mean distance in the antero-posterior and medio-lateral directions. An intra-class correlation coefficient test with one-way random model was performed to determine the reliability of different variables within-days and between-days. The results were presented in single measurement of intraclass correlation coefficient (ICC), the standard error of measurements, and the minimal detectable changes of each COP-related parameters. Results: The novel low-cost force plate demonstrates excellent reliability in terms of the COP velocity related parameters for within- and between-day measurements. The ICC of COP distance related parameters were good to excellent reliability for between-day measurements (range: 0.43–0.84). Older adults demonstrated excellent reliability in terms of the mean distance for antero-posterior and the results were better than those for younger participants for the eyes-opened and eyes-closed conditions. The reliability in terms of the mean distance for medio-lateral was poor to good for older adults (range: 0.38–0.55), and excellent for younger participants. Conclusion: The novel and low-cost force plate reliably measured balance and age affects the reliability of different COP variables, so the results of this study were pertinent to the selection of COP measures.